2018
DOI: 10.1007/s00405-018-5256-1
|View full text |Cite
|
Sign up to set email alerts
|

Flexible transnasal endoscopy with white light or narrow band imaging for the diagnosis of laryngeal malignancy: diagnostic value, observer variability and influence of previous laryngeal surgery

Abstract: Purpose Flexible transnasal endoscopy is a common examination technique for the evaluation of laryngeal lesions, while the use of narrow band imaging (NBI) has been reported to enhance the diagnostic value of white light endoscopy (WLE). The purpose of this study is to assess observer variability and diagnostic value of both modalities and investigate the possible influence of previous laryngeal surgery on the detection rates of laryngeal malignancy. Methods The study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 45 publications
1
21
0
2
Order By: Relevance
“…Only Ni et al 2 directly compared NBI to WLE and found NBI to be more accurate than WLE. This is also supported by studies comparing WLE to NBI in early glottic cancer, demonstrating NBI to be superior in accuracy 30,36 . The histological grading of leukoplakia varied among studies with some studies using WHO 2005 37 and others using the updated (WHO 2017), 6 with possible effects on the overall diagnosis, especially with differentiating severe dysplasia from CIS.…”
Section: Discussionmentioning
confidence: 89%
“…Only Ni et al 2 directly compared NBI to WLE and found NBI to be more accurate than WLE. This is also supported by studies comparing WLE to NBI in early glottic cancer, demonstrating NBI to be superior in accuracy 30,36 . The histological grading of leukoplakia varied among studies with some studies using WHO 2005 37 and others using the updated (WHO 2017), 6 with possible effects on the overall diagnosis, especially with differentiating severe dysplasia from CIS.…”
Section: Discussionmentioning
confidence: 89%
“…It could be assumed that the evaluation after TOLS should be easy because there are no postirradiation‐like changes in the tissues. In contrast, Davaris et al pointed out that the evaluation of endoscopic findings after previous surgical treatment may also be rather complicated. In our study, in most cases, the recurrent tumor appearance was different from the standard tumor appearance usually observed in previously untreated terrain.…”
Section: Discussionmentioning
confidence: 99%
“…Two reviewers summarized all data using standard forms. The diagnostic odds ratios (DORs), 4‐31,35‐37 summary receiver operating characteristic (SROC) curves, areas under the curves (AUCs), 4‐31,35‐37 and the extent of inter‐rater agreement 17,22,23,26 associated with NBI studies were evaluated, as was the (comparative) diagnostic accuracy of WLE. Each DOR was calculated as: (true positive (TP)/false positive [FP])/(false negative [FN]/true negative [TN]) with 95% confidence intervals (CIs); we used random‐effects models that considered both within‐ and between‐study variations.…”
Section: Methodsmentioning
confidence: 99%